The Reasons for UK Large Financial Institutions' Failure during the Recent Financial Crisis in 2007 - LI, ZHAOYI (2012)
Most UK financial institutions have failed during the recent financial crisis. Although this depression is triggered by the failure of US housing market, the business model for the UK is still different with US financial institutions. Most failed companies are not hold large amount of sub-prime loans in their asset portfolio in the UK, the most important reason is the wholesale funding strategies became the central business model for the most failed firms, therefore the retail deposits are no longer be an important funding source for most failed banks and building societies. And the Basel regulation cannot represent as a reasonable binding to constraint firm take risky project. Since the capital ratio for the most failed companies is good, but the capital still not absorb the contingent increasing liability for most failed companies. This paper will concentrates on evaluating the main reasons for the large UK financial institutions failed in both internal operation and external supervision. The empirical research will focus on the large commercial banks and building societies in the UK during the period from 2006 to 2011.